Knowledge, Attitude and Practice of Undergraduate Students Regarding Toothbrush Contamination and Disinfection - Swapna Bettanapalya Venkatesh1 , Vignesh Kamath2, Shibani Shetty3 , Smitha Sammith Shetty4* (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Toothbrushes play a significant role in disease transmission as they act as a reservoir formicroorganisms and aid in increasing the risk of infection in any individual. In recent years, the necessityof toothbrush disinfection has gained importance. Toothbrush disinfection should be recommended as aroutine practice for all individuals. This study aimed to assess the knowledge, attitude, and practice ofundergraduate students regarding toothbrush contamination and disinfection.Materials and methods: This study involved 446 undergraduate students between the age group of 18 to 23years. A validated questionnaire was used to assess the knowledge, attitude, and practice of undergraduatestudents regarding toothbrush contamination and disinfection. The study showed that 24.89% of the studentsdisinfected their toothbrushes and 75.11% did not use any disinfectant. 78.92% of the students feel thatbacteria as the main mode of toothbrush contamination. 84.40% of the students feel that the disinfection ofthe toothbrush is necessary whereas 15.69% feel that toothbrush disinfection is not necessary. 61.29% ofstudents did not know toothbrush disinfection.Conclusion: Fewer students have sufficient knowledge about toothbrush contamination and practice thedisinfection methods, whereas the majority of the students are unaware of the contamination of toothbrushesand the use of disinfectant methods.